#### paulthomasrowland

##### New member

- Joined
- Sep 24, 2015

- Messages
- 2

v2 = v1 (ln(h2/z0)/ln(h1/z0))

I cannot figure out for to solve for z0 correctly.

Can you help?

- Thread starter paulthomasrowland
- Start date

- Joined
- Sep 24, 2015

- Messages
- 2

v2 = v1 (ln(h2/z0)/ln(h1/z0))

I cannot figure out for to solve for z0 correctly.

Can you help?

- Joined
- Jun 18, 2007

- Messages
- 18,149

\(\displaystyle \displaystyle{\frac{v_2}{v_1} \ = \dfrac{ln(h_2)-ln(z_0)}{ln(h_1)-ln(z_0)}}\)

v2 = v1 (ln(h2/z0)/ln(h1/z0))

I cannot figure out for to solve for z0 correctly.

Can you help?

\(\displaystyle \displaystyle{\frac{v_2}{v_1} \ - \ 1\ = \dfrac{ln(h_2)-ln(z_0)}{ln(h_1)-ln(z_0)} \ - \ 1}\)

Now continue....

I would do it a slightly different way: Multiply though by ln(h1/z0)=ln(h1)-ln(z0) to get

v2 = v1 (ln(h2/z0)/ln(h1/z0))

I cannot figure out for to solve for z0 correctly.

Can you help?

v2 [ln(h1) - ln(z0)] = v1 [ln(h2) - ln(z0)]

or

v1 ln(z0) - v2 ln(z0) = v1 ln(h2) - v2 ln(h1)

and continue

- Joined
- Sep 24, 2015

- Messages
- 2

Very many thanks to you both